Malay Postcolonial Culture Narrative: Social Conflict In Anak Tanjung Play By Noordin Hassan: Naratif Budaya Pascakolonial Melayu: Konflik Sosial Dalam Drama Anak Tanjung oleh Noordin Hassan - Hussain Chin, Lena Farida; Ismail, Mardiana; Suhaimi, Nadhilah (PENDETA, 2023)
The revitalization of Malaysian theatre after the 1930s marked the beginning of the revival of Malaysian modern drama. Since then, the narrative, themes, genres, and performance elements of modern Malaysian drama have expanded to include a variety of forms, including postcolonial drama. Postcolonial drama is the first comprehensive study to examine how narratives have been instrumental in resisting imperialism's ongoing effects. This study employs contemporary theoretical frameworks derived from postcolonial studies to analyse a diverse range of dramatic plays. Postcolonial society is quite pressing, with numerous issues that squeeze between primordial culture and the new system (the new world). The manner of thinking and the ideology of decolonization influence the shape of culture in the practise of politics and social justice. This study uses qualitative methods that focus on textual and descriptive analysis. It will examine how the ideology in Anak Tanjung Malay by Noordin Hassan presents the issue of the oppression of the colonised society and the domination of the ruler over it. This research analyses the voice of the community expressed through the writer's point of view. Subsequently, the impact in question will be assessed through the lens of base and superstructure, as these frameworks centre around the cultural discourse around social strife. The findings indicate that social narrative is the central theme of this drama, which is characterised as a society-overwhelming struggle between the customary Malay culture systems and the new world.